1981
DOI: 10.1021/bi00523a019
|View full text |Cite
|
Sign up to set email alerts
|

Functional and structural studies on a tryptic fragment of eucaryotic elongation factor Tu from rabbit reticulocytes

Abstract: Treatment of eucaryotic elongation factor Tu (eEF-Tu; Mr 53 000) with trypsin results in cleavage of the factor at at least two sites, one and probably both of which are located near the amino-terminal end of the polypeptide chain. The products after exposure of eEF-Tu to trypsin for 2 h is a single polypeptide of 43 000 daltons (eEF-Tut) and as yet unidentified polypeptides of Mr less than or equal to 5000. The presence of high glycerol concentrations of GDP in the reaction mixture markedly retards the rate o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
28
0

Year Published

1983
1983
1992
1992

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 36 publications
1
28
0
Order By: Relevance
“…The partial amino acid sequence of EF-la from rabbit reticulocytes (14) and A. salina (15) was determined, and sequence conservation between A. salina EF-la and E. coli EF-Tu has been reported (15).…”
mentioning
confidence: 99%
“…The partial amino acid sequence of EF-la from rabbit reticulocytes (14) and A. salina (15) was determined, and sequence conservation between A. salina EF-la and E. coli EF-Tu has been reported (15).…”
mentioning
confidence: 99%
“…From our experimens with the 37/43-kDa tryptic fragments, it can be concluded that the proteolytic removal of the region spanning the residues 37 -68 and 37 -128 completely abolished the transport of aminoacyl tRNA to the ribosome. However, in two other reports, tryptic removal of residues 37 -68 in EF-la solely reduces the aminoacyl tRNA binding to only 30% and 6O%, respectively [16,171. The larger reduction in our experiments (to lo%), obtained on a mixture of the 37-kDa and 43-kDa fragments, could be due to the additional presence of the 37-kDa fragment lacking the residues 37 -128 and having no tRNA binding activity at all.…”
Section: Discussionmentioning
confidence: 81%
“…Limited digestion experiments have already been described with eukaryotic EF-la [16,171, which revealed digestion patterns reminiscent of prokaryotic EF-Tu from Escherichiu coli [18,191 and Thermus thermophilus [20]. A major difference between EF-Tu and EF-la concerns the exchange of proteinbound guanine nucleotides.…”
mentioning
confidence: 99%
“…On removal of heme, the region around Asp-47 also shows increased accessibility to proteolysis. We have observed that HbA is very resistant to V8 protease digestion (17). In the tetrameric Hb none of the glutamyl/ aspartyl peptide bonds of a-or P-chain is accessible to V8 protease digestion.…”
Section: Discussionmentioning
confidence: 84%
“…Polyhydric alcohols, like ethylene glycol and glycerol, have been reported to stabilize the protein structure (cryoprotectants; ref. 16), and in some cases these have been shown to limit the proteolytic digestion of proteins (17). Furthermore, glycerol is the widely used solvent to induce proteases to reform peptide bonds in the fragment-complementing systems (7).…”
Section: Methodsmentioning
confidence: 99%